2018
DOI: 10.1016/j.pbiomolbio.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Cause of Cambrian Explosion - Terrestrial or Cosmic?

Abstract: We review the salient evidence consistent with or predicted by the Hoyle-Wickramasinghe (H-W) thesis of Cometary (Cosmic) Biology. Much of this physical and biological evidence is multifactorial. One particular focus are the recent studies which date the emergence of the complex retroviruses of vertebrate lines at or just before the Cambrian Explosion of ∼500 Ma. Such viruses are known to be plausibly associated with major evolutionary genomic processes. We believe this coincidence is not fortuitous but is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 122 publications
3
20
0
1
Order By: Relevance
“…A rapidly growing body of evidence from within biology itself, as well as from geology, astronomy and space research, is now converging towards a vindication of the HoyleWickramasinghe theory of the origin and evolution of cosmic life (Steele et al, 2017) [11]. In a comprehensive review article Steele et al [11] have shown that this long-resisted paradigm shift is well under way at the present time. The arrival of Oumuamua (A/2017U1) may coincide with the ushering in of a new transformative paradigm in science.…”
Section: Discussionmentioning
confidence: 99%
“…A rapidly growing body of evidence from within biology itself, as well as from geology, astronomy and space research, is now converging towards a vindication of the HoyleWickramasinghe theory of the origin and evolution of cosmic life (Steele et al, 2017) [11]. In a comprehensive review article Steele et al [11] have shown that this long-resisted paradigm shift is well under way at the present time. The arrival of Oumuamua (A/2017U1) may coincide with the ushering in of a new transformative paradigm in science.…”
Section: Discussionmentioning
confidence: 99%
“…The Greek philosopher Anaxagoras considered this in the 5 th -century BC, and later also scientists including Francis Crick and Leslie Orgel [128] even hypothesized that life on Earth may have been deliberately seeded by extraterrestrial civilizations. Recently the idea was repeated by Steele et al, who considered an extraterrestrial origin of retroviruses during the Cambrian explosion about 541 Mya when life diversified at an enormous speed [129]. The authors also discussed the SARS coronavirus as originating from space.…”
Section: Spores and Survival Under Extreme Conditionsmentioning
confidence: 99%
“…There are arguments against it because radiation from space over long distances would not allow traveling of living entities like life on earth. The pansperm theory still has many followers today [27,28]. There are meteorites which contain up to 90 amino acids, even though we have only 20 as the basis of life on Earth.…”
Section: Are Viruses Alive? Can They Be the Origin Of Life? Will Theymentioning
confidence: 99%